Urgensi Aplikasi Teknologi dalam Pendidikan di Indonesia - Miko Trenggono Hidayatullah; Masduki Asbari; Muhammad Iqbal Ibrahim; Ahmad Hadidtia Haekal Faidz (Journal of Information Systems and Management (JISMA), 2023)
The objective of this study is to investigate various technologies that can be implemented in the context of education in Indonesia. This research report employs a qualitative descriptive method by conducting a listening and note-taking approach, as the data source is derived from listening to the oral narration on the YouTube channel Jabfung PTP titled "What Is Technology, How Does It Contribute to Better Education," presented by Prof. Dr. Achmad Nizar Hidayanto, S.Kom, M.Kom, Faculty of Computer Science, University of Indonesia. The findings of this study elucidate that the world is continuously evolving. In the past, learning required reading books, but in this digital revolution era, we can learn using our smartphones. This research initiative stems from the rise of the digital revolution that can be harnessed in the field of education. The digital revolution has the potential to transform the educational landscape in Indonesia for the better.